The anatomy, neurophysiology, and cellular mechanisms of intradental sensation - Ronan, Elizabeth A.; Nagel, Maximilian; Emrick, Joshua J. (Frontiers in Pain Research, 2024)
Somatosensory innervation of the oral cavity enables the detection of a range of environmental stimuli including minute and noxious mechanical forces. The trigeminal sensory neurons underlie sensation originating from the tooth. Prior work has provided important physiological and molecular characterization of dental pulp sensory innervation. Clinical dental experiences have informed our conception of the consequence of activating these neurons. However, the biological role of sensory innervation within the tooth is yet to be defined. Recent transcriptomic data, combined with mouse genetic tools, have the capacity to provide important cell-type resolution for the physiological and behavioral function of pulp-innervating sensory neurons.Importantly, these tools can be applied to determine the neuronal origin of acute dental pain that coincides with tooth damage as well as pain stemming from tissue inflammation (i.e., pulpitis) toward developing treatment strategies aimed at relieving these distinct forms of pain.